The Role of Sub-District Head in the Resolution of Social Conflict through Local Interference in South-East Sulawesi Province - Firdaus Arifin (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This research is entitled The Role of the Camat in the Settlement of Social Conflictsthrough Local Wisdom in Katobu District, Muna Regency, Southeast Sulawsi Province.This research is motivated by the authors' interest in examining the problems that ariseregarding the Role of the Camat in Settling Social Conflicts through Local Wisdom.The research method used in the preparation of this thesis is a qualitative researchmethod with a descriptive approach. Data obtained through data collectiontechniques: observation, interviews, and documentation. The results of this studyindicate that local wisdom has been used by the Katobu District Head in the resolutionof social conflicts in Katobu District, Muna Regency, Southeast Sulawesi Province.Local wisdom that is often used by the Katobu District Head in resolving SocialConflicts includes: Negotiations have been carried out through mutual consultation,Mediation has been carried out through the Kabali Tradition which is a tool to createharmony and peace, Arbitration is not carried out because the conflicting communitywants the resolution of the conflict through mutual consultation